Combined standard immunosuppression and immune checkpoint inhibition for BKPyV+ metastatic renal cell carcinoma of the graft in a kidney transplant recipient with chronic rejection: a case report - Gandolfini, Ilaria; Manini, Martina; Benigno, Giuseppe Daniele; Gentile, Micaela; Palmisano, Alessandra; Somenzi, Danio; Gnetti, Letizia; Delsante, Marco; Mordà, Benedetta; D’Angelo, Marta; Salvetti, Daniel; Fiaccadori, Enrico; et al. (Frontiers in Oncology, 2025)
We report on the first case of a dual-kidney transplant recipient diagnosed with a metastatic BK polyomavirus-positive clear renal cell carcinoma with sarcomatoid features, which caused extensive vena cava thrombosis. The patient was successfully treated with the immune checkpoint inhibitors (ICIs) ipilimumab plus nivolumab and continued immunosuppression with tacrolimus, mycophenolate, and steroids. He received ICIs despite the presence of graft dysfunction due to transplant glomerulopathy. As expected, the ICI treatment caused a progressive but asymptomatic decline of the graft function, which resulted in end-stage kidney disease. However, continuation of a full immunosuppression prevented acute rejection, graft intolerance syndrome episodes, or dual graft nephrectomy, which enabled the patient to successfully continue ICIs while on dialysis and to achieve sustained partial remission at the 17-month follow-up.